CFD-DEM simulations of a fluidized bed crystallizer. (29th June 2017) - Kerst, Kristin; Roloff, Christoph; Medeiros de Souza, Luís G.; Bartz, Antje; Seidel-Morgenstern, Andreas; Thévenin, Dominique; Janiga, Gábor
Highlights: Examination of the complex two-phase flow in a fluidized bed crystallizer. CFD-DEM simulation of the crystallizer with non-growing crystals. Validation of the CFD-DEM simulation model via Shadowgraphy with a particle tracking approach. Identification of regions with unfavorable hydrodynamic features, thus negatively impacting process outcome. Determination of crystal position and relative crystal velocities within the crystallizer. Abstract: In the present study, important features of the two-phase flow in a fluidized bed crystallizer are examined by numerical computations and companion experiments. The simulations are carried out using a coupled CFD-DEM approach (CFD: Computational Fluid Dynamics; DEM: Discrete Element Method). After validating an open-source CFD-DEM software tool for this purpose, regions within the crystallizer with unfavorable hydrodynamic features and thus a negatively impacted process outcome have been identified. This was first accomplished by single-phase CFD simulations. Then, the validated CFD-DEM model delivers valuable information that is difficult or even impossible to measure experimentally with sufficient accuracy, such as the velocity and position of fluidized crystals within the crystallizer. Since the simulations are computationally challenging, a compromise between simulated process time and number of simulated particles must be found. Hence, the CFD-DEM simulations are not utilized to simulate the whole crystallization process, but to examine a short time-window in detail. Corresponding findings confirm proper fluidization of the crystals support the model reduction carried out in a parallel project.